Incorporation of chlorhexidine gluconate or diacetate into a glass-ionomer cement: porosity, surface roughness, and anti-biofilm activity - Marti, Luana Mafra [UNESP]; Becci, Ana Carolina de Oliveira[UNESP]; Palomari Spolidorio, Denise Madalena [UNESP]; Brighenti, Fernanda Lourenção [UNESP]; Giro, Elisa Maria Aparecida [UNESP]; Zuanon, Angela Cristina Cilense [UNESP] (My University, 2014)
To evaluate the porosity, surface roughness and anti-biofilm activity of a glass-ionomer cement (GIC) after incorporation of different concentrations of chlorhexidine (CHX) gluconate or diacetate. Methods: For the porosity and surface roughness tests, 10 test specimens were fabricated of the GIC Ketac Molar Easy Mix (KM) and divided into the following groups: Control, GIC and 0.5% CHX diacetate; GIC and 1.0% CHX diacetate; GIC and 2.0% CHX diacetate; GIC and 0.5% CHX gluconate; GIC and 1.0% CHX gluconate; GIC and 2.0% CHX gluconate. To evaluate porosity, the test specimens were fractured. The fragments were photographed by scanning electron microscopy (SEM), and the images analyzed with the aid of the software program Image J. The surface roughness (Ra) was obtained by the mean value of three readouts performed on the surface of each specimen, always through the center. To analyze the anti-biofilm activity, strains of S. mutans ATCC 35688 were used, and the groups control and GIC +CHX diacetate 1% were divided as follows: GIC (1 day); GIC (7 days), GIC (14 days), GIC (21 days); GIC+CHX (1 day), GIC+CHX (7 days), GIC+CHX (14 days), GIC+CHX (21 days); GIC+ CHX (1 day), GIC+ CHX (7 days), GIC+ CHX (14 days) and GIC+ CHX (21 days) using 10 test specimens per group. For biofilm growth, the specimens were placed in a vertical position in 24-well plates and incubated overnight 10 times. The culture medium was renewed every 24 hours. The suspension was diluted and seeded on BHI agar for quantification of the bacteria present. For evaluation of all the tests the two-way ANOVA was used, and if necessary, the Tukey test was applied, with a level of significance of 5%. Results: Regarding GIC porosity, the ANOVA showed that the presence of CHX increased the porosity (P< 0.001) proportionally to the increase in concentrations (P= 0.001), without however, presenting interaction between material and concentration (P= 0.705). Regarding the number of pores, a significant increase in pores was observed with the increase in CHX concentration (P= 0.003). The surface roughness test demonstrated no statistically significant effect as to increase or reduction in roughness at any of the CHX concentrations used (P> 0.05). Anti-biofilm activity analysis pointed out a significant effect of the factors material (P= 0.006) and time (P< 0.001), with CHX diacetate CHX presenting greater effectiveness in reducing microorganisms.
Keywords: Physical-properties; Mechanical-properties; Streptococcus-mutans; In-vivo; Antibacterial activity; Restorative materials; Art restorations; Fluoride release; Microorganisms; Invitro